2019
DOI: 10.3835/plantgenome2018.12.0096
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Complex Genome of Crested Wheatgrass by Chromosome Flow Sorting

Abstract: Core Ideas Flow sorting enabled to dissect the genome of crested wheatgrass into chromosomes. This is a powerful approach to access the complex genome of a wheat wild relative. Chromosome genomics will support alien introgression breeding of the crop. Wheatgrass (Agropyron sp.) is a potential source of beneficial traits for wheat improvement. Among them, crested wheatgrass [A. cristatum (L.) Gaertn.] comprises a complex of diploid, tetraploid, and hexaploid forms with the basic genome P, with some accessions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 128 publications
(164 reference statements)
1
17
0
Order By: Relevance
“…Our results based on the chromosomal location of COS markers may indicate that chromosomal inversions are more abundant in the P genome of tetraploid A. cristatum than those of the diploid form, which could be the consequence of the polyploidization-induced genome reorganization (Ma et al 2004; Han et al 2005, 2017; Zhang et al 2013). In line with these studies, Said et al (2019) observed differences in the FISH signal pattern between chromosomes flow sorted from the diploid and tetraploid accessions, and the differences were more pronounced on the chromosomes flow sorted from tetraploid A. cristatum . A recent development in the flow-cytometric sorting of P genome chromosomes from the wheat– A. cristatum addition and ditelosomic lines opens the way for shot gun sequencing and high-resolution structure analysis of A. cristatum chromosomes (Said et al 2019).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Our results based on the chromosomal location of COS markers may indicate that chromosomal inversions are more abundant in the P genome of tetraploid A. cristatum than those of the diploid form, which could be the consequence of the polyploidization-induced genome reorganization (Ma et al 2004; Han et al 2005, 2017; Zhang et al 2013). In line with these studies, Said et al (2019) observed differences in the FISH signal pattern between chromosomes flow sorted from the diploid and tetraploid accessions, and the differences were more pronounced on the chromosomes flow sorted from tetraploid A. cristatum . A recent development in the flow-cytometric sorting of P genome chromosomes from the wheat– A. cristatum addition and ditelosomic lines opens the way for shot gun sequencing and high-resolution structure analysis of A. cristatum chromosomes (Said et al 2019).…”
Section: Discussionmentioning
confidence: 56%
“…In line with these studies, Said et al (2019) observed differences in the FISH signal pattern between chromosomes flow sorted from the diploid and tetraploid accessions, and the differences were more pronounced on the chromosomes flow sorted from tetraploid A. cristatum . A recent development in the flow-cytometric sorting of P genome chromosomes from the wheat– A. cristatum addition and ditelosomic lines opens the way for shot gun sequencing and high-resolution structure analysis of A. cristatum chromosomes (Said et al 2019).…”
Section: Discussionmentioning
confidence: 56%
“…Prior to the flow cytometric analysis, the chromosomes were labeled by fluorescence in situ hybridization in suspension (FISHIS) using 5′-FITC-GAA 7 -FITC-3′ oligonucleotides (Sigma, Saint Louis, MO, United States) according to Giorgi et al ( 2013 ) and stained by DAPI (4′,6-diamidino 2-phenylindole) at 2 μg/ml. Chromosome analysis and sorting were carried out using a FACSAria II SORP flow cytometer and sorter (Becton Dickinson Immunocytometry Systems, San José, CA, United States) as described by Molnár et al ( 2016 ) and Said et al ( 2019 ). Bivariate flow karyotypes FITC vs. DAPI fluorescence were acquired for each sample and two batches of 25,000–76,000 copies of each chromosome were sorted into PCR tubes containing 40 μl sterile deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…Agropyron cristatum (GAA) 7 [42] Dasypirum villosum (H. villosa) (GAA) 7 [61] Dasypyrum villosum (H. villosa) pTa71 (rDNA) [74] Triticum aestivum (GAA) 7 (AG) 12 [61] Triticum aestivum (GAA) 7 [75] Triticum aestivum (transgenic lines) (GAA) 7 [76] Triticum. dicoccoides (GAA) 7 [52] Triticum durum (AG) 12 (AAT) 7 (AAC) 5 [61] Triticum durum (AG) 12 [74] Triticum militinae (GAA) 7 [51] Triticum monococcum (ACC) 5 + (GAA) 7 [50] Triticum timopheevii (GAA) 7 Unpublished F I G U R E 5 Setting sort windows (red rectangles) to isolate particular chromosomes from bread wheat (Triticum aestivum, 2n = 6x = 42) cv.…”
Section: Species Probe Referencementioning
confidence: 99%